Theranostics: From PET imaging to radioisotope therapy - Watabe, Tadashi (Drug Delivery System, 2025)
Theranostics is an innovative medical technology that integrates both therapeutic and diagnostic capabilities, allowing seamless transition from imaging diagnosis to radioisotope therapy by altering the radionuclide label on the same compound. This approach enables not only the quantitative assessment of target molecule expression in diagnostic imaging but also the prediction of therapeutic efficacy. In the drug discovery process, theranostics provides insights into the biodistribution of diagnostic agents, facilitating the optimization of therapeutic agents. This optimization can reduce physiological accumulation in normal organs, thereby minimizing potential side effects. Japan has taken a leading role globally in developing and clinically applying theranostics using astatine（211At）, a radionuclide that can be produced using cyclotrons. The advancement of 211At-based drug development offers significant potential for future theranostic applications, with expectations for expanded clinical use and therapeutic innovation.